The emergence of transnational responses to corruption in international arbitration. (16th April 2019) - Gaillard, Emmanuel
Abstract: As the global fight against corruption continues to intensify, arbitrators play an increasingly important role in developing responses to cases raising corruption issues. The present article investigates the steady emergence of general principles, or transnational rules, which are available to and increasingly applied by arbitrators who adjudicate corruption issues. First, in light of the difficulty of deducing direct evidence of corruption, arbitrators have consistently accepted that corruption can be proven through a sufficient number of indicia, or 'red flags' of corruption. Second, in certain circumstances, arbitrators and courts may depart from the traditional rule that refuses to restore benefits performed under contracts tainted by corruption. Third, a number of cases have affirmed that issues of corruption are to be resolved by reference to rules of transnational public policy, rather than local mandatory rules, or lois de police, where local rules do not form part of the lex contractus . While such responses to corruption have not and need not achieve unanimous recognition in all legal systems, they have been adopted in a significant number of cases to function as general principles that can guide arbitrators dealing with corruption issues.